Peran Ganda Hakim Sebagai Mediator Bagi Penyelesaian Perkara Perdata Di Pengadilan Terkait Kode Etik Profesi - Dely Bunga Saravistha (Jurnal Ilmiah Raad Kertha, 2020)
The integration of mediation by the Supreme Court Regulation No. 1 of2016 on Mediation Procedure Court (hereinafter called Perma 1 of 2016) has given newduties and responsibilities of judges, which in addition to being a judge is also requiredto perform the function of mediator. Mediator and Judge are both legal profession, eachof which has a Code of Ethics and professional characteristics. This research is anormative law, the legal research that lay down the law as a system of building norms inthe form of principles, norms, rules of law, court decisions, agreements and doctrines ofexperts. Perma existence in 2016 has made judges have dual roles that are mutuallycontradictory. The impact of the position and the dual role of judges in the courts is anaccumulation of case files still occur because of the number of judges is not proportionalto the intensity of incoming cases and also due to judges who dominate the judicialmediation process is still very rare to see success. So that the existence of mediation onlybe impressed stalling settling disputes.